2011
DOI: 10.4028/www.scientific.net/jera.5.16
|View full text |Cite
|
Sign up to set email alerts
|

The Optimization of Ball Milling Method in Preparation of Phenolic/Functionalized Multi-Wall Carbon Nanotube Composite and Comparison with Wet Method

Abstract: This paper focuses on the optimization of ball milling as a dry mixing method and comparison with the wet method for manufacturing phenolic/multi-wall carbon nanotube (MWCNT) composites. In the ball milling, the effect of milling-time on the properties of composites containing functionalized and pristine MWCNT in two MWCNT concentrations has been investigated. At first in the wet method, polymer was dissolved in acetone and then mixed with MWCNT by sonication method. Also, the effect of functionalization by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…In addition, wet mixing also showed less thermal stability than dry milling method. 168 This result strengthened the previous reported work by Mathur and coworkers. However, these presented results were contradicted by another study exhibited by Chaiwan and Pumchusak that for both wet and dry dispersion method improved mechanical properties, where a comparative study conducted, and in wet method the addition of 1 wt% MWCNT provided flexural and tensile properties improvement of 29% and 19%, whereas in the dry method with same MWCNT wt% inclusion, the flexural and tensile properties enhancement recorded with 14% and 24% hike respectively, indicating the wet dispersion method has better enhancement than the dry method.…”
Section: Nanocarbon Modifier (Wt%)supporting
confidence: 90%
“…In addition, wet mixing also showed less thermal stability than dry milling method. 168 This result strengthened the previous reported work by Mathur and coworkers. However, these presented results were contradicted by another study exhibited by Chaiwan and Pumchusak that for both wet and dry dispersion method improved mechanical properties, where a comparative study conducted, and in wet method the addition of 1 wt% MWCNT provided flexural and tensile properties improvement of 29% and 19%, whereas in the dry method with same MWCNT wt% inclusion, the flexural and tensile properties enhancement recorded with 14% and 24% hike respectively, indicating the wet dispersion method has better enhancement than the dry method.…”
Section: Nanocarbon Modifier (Wt%)supporting
confidence: 90%
“…Taherian et al also revealed that the BM time of 2 h positively affects the distribution of CNTs in the polymer composite. 79 In this context, the homogeneous distribution of CNTs in nanocomposites increased the uniformity of stress distribution and exhibited better mechanical performance than other nanocomposites. Also, due to the addition of CNTs, interlocking effect was formed between the GF and the matrix, the shear delamination of the hybrid nanocomposite was reduced and enhanced mechanical properties were obtained.…”
Section: Sem-edsmentioning
confidence: 99%
“…Botelho et al supported that strong hydrogen interaction between the hydroxyl groups of the MWCNTs and the matrix allows the MWCNT dispersed in the phenolic resin [44] to be bonded covalently [15]. According to Taherian et al, the existence of -COOH peaks from the Fourier transform infrared spectroscopy study is an indication of the bonding and crosslinking formation between the MWCNT and the phenolic resin [18] as shown in Figure 7. When the CR fiber was added as much as 40 wt.%, the tensile strength and modulus of the MWCNT-phenolic composites improved as much as 6% and 18%, respectively.…”
Section: Physical Properties Of Cr Fiber-reinforced Mwcnt-phenolic Compositesmentioning
confidence: 99%
“…A previous study reported that a drymixed dispersion of 2 volume % of MWCNT in a Novolac-type phenolic resin after 25 h of ball milling exhibited a substantial improvement in flexural strength compared to a wet-mixed dispersion [16]. However, wet ultrasonication is restricted to soluble and low viscous polymers [17] and it induces modifications in structural changes to the polymer, which may weaken the composite's mechanical and physical properties [18]. Eslami et al reported that the flexural strength and thermal stability of phenolic composites increase with the increase in MWCNT up to 0.5 wt.% and decrease at 2 wt.% [19].…”
Section: Introductionmentioning
confidence: 99%